2D Electronics: Origin of the Threshold Voltage Shift in a Transistor with a 2D Electron Gas Channel at the Al2O3/SrTiO3 Interface (Adv. Electron. Mater. 6/2020). (4th June 2020) - Moon, Taehwan; Lee, Hyun Jae; Hyun, Seung Dam; Kim, Baek Su; Kim, Ho Hyun; Hwang, Cheol Seong
Abstract : A transistor with a two‐dimensional electron gas (2DEG) channel at the hetero‐oxide structure is proposed by Cheol Seong Hwang and co‐workers in article number 1901286 . The negative voltage stress on the gate induces the migration of oxygen vacancies through the gate oxide, resulting in a feasible 2DEG conductance for transistor operation. This will contribute to understanding the principles of 2D electronic devices.